Isolation and Characterization of a Carotenoid-Associated Thylakoid Protein from the Cyanobacterium Anacystis nidulans R2 - Masamoto, Kazumori (1987)
A carotenoid-associated membrane protein was isolated from Anacystis nidulans R2 thylakoids. Sodium pyrophosphate and sodium bromide washed thylakoids were solubilized with the nonionic detergents dodecyl-β-D-maltoside and octyl-β-D-glucopyranoside, and these detergent extracts were fractionated on a sucrose density gradient. A yellow fraction from the sucrose gradient was further purified by anion-exchange and organomercuric-affinity column chromatography to yield a fraction virtually free of chlorophyll and highly enriched in both carotenoids and a 42 kilodalton polypeptide. Evidence presented in this paper suggests that the carotenoid-containing 42 kilodalton protein is thylakoid associated rather than cytoplasmic membrane associated. The purified 42 kilodalton polypeptide was used to raise polyclonal antibodies in rabbits. Immuno-chemical detection of the 42 kilodalton polypeptide on Western blots demonstrated an increased accumulation of this polypeptide in cells grown under high-light conditions relative to cells grown under low light.